Assessment of the Incidence of Hemi-Diaphragmatic Paralysis Following Infraclavicular and Supraclavicular Approaches for Brachial Plexus Block: A Randomized Controlled Study - Aruna Parameswari; Anisha Pauline Paul; Krithika U (Turkish Journal of Anaesthesiology and Reanimation, 2025)
Objective: With the regional anaesthetic technique used for brachial plexus block, the phrenic nerve (C3-C5) can be blocked due to its anatomical proximity to the brachial plexus and the effect of a significant volume of local anaesthetic deposited near the nerve roots. The goal of this study was to compare the incidence of hemi-diaphragmatic paralysis (HDP) following infraclavicular and supraclavicular approaches for brachial plexus block, using a low-volume local anaesthetic. Methods: A total of 60 patients were enrolled in this study: 30 patients were assigned to the supraclavicular brachial plexus block group, and 30 patients were assigned to the infraclavicular brachial plexus block group. Under aseptic precautions and ultrasound guidance, both groups received 20 mL of 0.5% bupivacaine. The diaphragmatic excursion was measured using ultrasound before the block and 2 hours afterward in the postoperative care unit. A reduction in excursion of more than 75% compared with pre-block values was considered complete paralysis, whereas a reduction of 25-75% was considered partial paralysis. Results: Infraclavicular brachial plexus block (3.33%) had a lower incidence of HDP compared with supraclavicular brachial plexus block (36.66%). The complications in both groups were not significant, and there was no need to use general anaesthesia. Conclusion: The incidence of phrenic nerve palsy in the supraclavicular and infraclavicular brachial plexus groups was low, with a lower incidence of HDP in the infraclavicular group.